Lake effect on summer cooling of shorelines and adjacent inland forests on Lake Superior's north shore ... - Hillman, Ashley; Nielsen, Scott (Zenodo, 2023)
Climate refugia, or areas that are projected to remain relatively stable under climate change, can serve as remnant habitat or steeping stones for species dispersal. The largest freshwater lake in the world by surface area, Lake Superior, serves as a model system for understanding cooling-mediated local refugia, as its cool summer water temperatures and wave action have maintained shoreline habitats suitable for disjunct opulations for arctic-alpine plants since deglaciation. It is known to affect local climates by providing a summer cooling effect near its shorelines, however, the inland gradient of change and spatial patterns of cooling has not been quantified. Here, we describe the extent of the inland cooling gradient, the degree of temperature buffering, and patterns of cooling for Lake Superior's north shore over a 3-year period. Specifically, we established 7 transects along Lake Superior's north shore, with temperature data loggers placed at 10 m, 100 m, 1 km, 10 km, and 100 km inland. We analyzed ... : Funding provided by: Natural Sciences and Engineering Research CouncilCrossref Funder Registry ID: https://ror.org/01h531d29Award Number: ...